Measuring attitudes towards voluntary childlessness: Indicators in European comparative surveys - Ivett Szalma; Marieke Heers; Maria Letizia Tanturri (PLoS ONE, 2025)
The prevalence of voluntary childlessness is rising in Europe, likely accompanied by growing social acceptance. However, more evidence is needed on how to measure this acceptance in comparative surveys. This study examines two dimensions of voluntary childlessness: prescriptive and proscriptive. The aim of this study is to show how the two dimensions differ in measuring voluntary childlessness and to highlight the factors that shape these attitudes. Findings reveal that socio-demographic variables relate differently to the two dimensions of the acceptance of voluntary childlessness for men and women. At the macro level, lower gender inequality predicts higher acceptance of voluntary childlessness across both dimensions. Conversely, higher childlessness rates are associated with favourable attitudes only in the prescriptive dimension, while country-level religiosity does not predict either dimension. The study underscores the importance of distinguishing between dimensions of voluntary childlessness, as different factors shape their acceptance. Additionally, no differences emerge in attitudes toward voluntary childlessness for males and females.